2019
DOI: 10.1111/ajt.15309
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mitochondria in organ donors promote allograft rejection

Abstract: The innate immune system is a critical regulator of the adaptive immune responses that lead to allograft rejection. It is increasingly recognized that endogenous molecules released from tissue injury and cell death are potent activators of innate immunity. Mitochondria, ancestrally related to bacteria, possess an array of endogenous innate immune activating molecules. We have recently demonstrated that extracellular mitochondria are abundant in the circulation of deceased organ donors and that their presence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 65 publications
6
44
0
Order By: Relevance
“…The role of IR-induced mitochondrial damage as one of the key contributors in allograft functions is increasingly recognized [ 19 , 20 , 21 ]. Our research group previously demonstrated that SCS of heart grafts resulted in decreased mitochondrial oxidative phosphorylation capacity and cytochrome c release, together with increased transcription of proapoptotic proteins [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of IR-induced mitochondrial damage as one of the key contributors in allograft functions is increasingly recognized [ 19 , 20 , 21 ]. Our research group previously demonstrated that SCS of heart grafts resulted in decreased mitochondrial oxidative phosphorylation capacity and cytochrome c release, together with increased transcription of proapoptotic proteins [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular mitochondria led to the upregulation of endothelial cell (EC) adhesion molecules, inflammatory cytokines and chemokines, and activated dendritic cells to upregulate costimulatory molecules. They concluded that ccf-mtDNA from organ donors may directly activate allograft ECs, and result in graft rejection in transplant recipients [ 145 ].…”
Section: Mtdna In Trauma and Organ Transplantationmentioning
confidence: 99%
“…Mitochondria treated endothelial cells had a higher adherence of allospecific T cells. Coincubation of Human aortic endothelial cells (HAECs) with mitochondria from HeLa cells resulted in an upregulation of CD54, CD106 and CD62E and an increased production of IL-6, IL-8 and MCP-1 [ 151 ]. Coincubation of murine mitochondria with dendritic cells resulted in an up regulation of CD40 and CD86 as well as MHC II.…”
Section: Safety Of Mitochondrial Transplantationmentioning
confidence: 99%
“…Coincubation of murine mitochondria with dendritic cells resulted in an up regulation of CD40 and CD86 as well as MHC II. Additionally co-incubation of human PBMCs with mitochondria treated ECs resulted in increased numbers of effector (IFNγ+, TNFα+) CD8+ T cells [ 151 ]. Also, other studies report on inflammatory responses to mitochondria, for example, when activated platelet-derived mitochondria where given intravenously causing transferation to neutrophils and cytokine production or when lymphoblast derived mitochondria led to the modulation of cytokine production in macrophages and dendritic cells [ 152 ].…”
Section: Safety Of Mitochondrial Transplantationmentioning
confidence: 99%